2021
DOI: 10.1109/access.2021.3072224
|View full text |Cite
|
Sign up to set email alerts
|

Directed EEG Functional Connectivity Features to Reveal Different Attention Indexes Using Hierarchical Clustering

Abstract: Functional connectivity related to familiarity has recently been investigated in the context of various stimuli (e.g., words, faces, pictures, music, and video). However, the directed functional connectivity patterns with different attention indexes as a response to familiar/unfamiliar stimuli remain unclear. In the current study, we employed the Directed Transfer Function (DTF) to estimate the information flow between brain areas. This method was reported to be practically robust to volume conduction. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…As the diversity of feature importance implied functional differentiation among regions during the emergence of consciousness, we next sought to uncover the hidden functional structure of these regions by taking advantage of the similarity of feature importance. We used a hierarchical clustering algorithm, which belongs to the data-driven unsupervised machine learning approach, 32 to cluster these 20 regions by their feature importance values. We found these regions were automatically clustered into three groups in both transitions ( Figure 6 D for NS versus SubCon and Figure 6 E for SubCon versus Con).…”
Section: Resultsmentioning
confidence: 99%
“…As the diversity of feature importance implied functional differentiation among regions during the emergence of consciousness, we next sought to uncover the hidden functional structure of these regions by taking advantage of the similarity of feature importance. We used a hierarchical clustering algorithm, which belongs to the data-driven unsupervised machine learning approach, 32 to cluster these 20 regions by their feature importance values. We found these regions were automatically clustered into three groups in both transitions ( Figure 6 D for NS versus SubCon and Figure 6 E for SubCon versus Con).…”
Section: Resultsmentioning
confidence: 99%
“…Frontal lobe and central lobe play an important role in attention processing [72]. Many EEG studies have found frontal asymmetry existed in the patients with depression.…”
Section: Abnormal Brain Symmetry In MDmentioning
confidence: 99%